Application of Traditional Chinese Medicine soaking-bath technique for a patient with chronic renal failure of spleen-kidney Yang deficiency type (中药泡洗技术在1例脾肾阳虚型慢性肾衰竭患者中的应用) - WU Chunli (吴春丽); TANG Ling (唐玲); DENG Jianhua (邓建华) (中西医结合护理)
This paper reviewed the clinical data of a patient with c chronic renal failure of spleen-kidney Yang deficiency type, analyzed the application effect of Traditional Chinese Medicine (TCM) soaking-bath technique in relief of fatigue and swelling symptoms, and summarized the operation method and related nursing measures. Based on the comprehensive nursing assessment and basic care, the TCM soaking-bath therapy is effective in relief of fatigue and swelling symptom of the patient with chronic renal failure. (本文回顾1例脾肾阳虚型慢性肾衰竭患者临床资料, 分析中药泡洗缓解乏力、水肿症状的作用, 总结中药泡洗技术实施方法和相关护理经验。在完善护理评估和常规护理的基础上, 实施中药泡洗技术能够缓解脾肾阳虚型慢性肾衰竭患者乏力、水肿症状。)